A Real-Time Web Observatory for Cycling Safety: A Tool for Supporting Research and Decision Making of People and Organizations - Bonacic-Castro, C; Gonzalez-Ibanez, R (John Wiley and Sons Inc, 2015)
Human-generated content on the Web has increased over the last decade. In part, this situation has been powered by the proliferation of social networking services and mobile computing. In the context of citizen safety, everyday people share information about safety-related events such as natural disasters, accidents, and theft. This information can have valuable implications for the community and authorities, however, processing and making sense of such volume of information are difficult tasks for machines and likely impossible for humans. This poster shows the design of a real-time Web observatory that uses publicly available information found in social networking services such as Twitter to automatically provide visualizations and indicators of safety-related events for the particular case of cyclists as perceived by the citizens. We demonstrate the potential applications of this design with two implementations thought to aid researchers, decision makers, and people in general. Copyright © 2015 Roberto González-Ibáñez, Carolina Bonacic, and Álvaro Fernández of Universidad de Santiago de Chile.